Adsorption Behaviour of Cr(III) Ions on Sepiolite - Asçi, Y.; Berkan, P. (Asian Journal of Chemistry, 2010)
Removal of Cr(III) ions from waste waters is essential due to their toxicity. In the present study, batch sorption experiments were carried out to evaluate the performance of sepiolite in the removal of Cr(III) from aqueous solution. The sorption of Cr(III) from aqueous solution with sepiolite was studied at varying Cr(III) concentration, adsorbent dose, pH, contact time and temperature. The results obtained from equilibrium adsorption studies are fitted in various adsorption models such as Langmuir and Freundlich and the adsorption was well described by the Freundlich adsorption isotherm model. Thermodynamic parameters, free energy (ΔGº), enthalpy (ΔHº) and entropy (ΔSº) of adsorption were also calculated. Furthermore, the Lagergrenfirst- order, pseudo-second-order and the intraparticle diffusion models were used to describe the kinetic data. The experimental data fitted well the Lagergren-first-order.